Sistem Keamanan Sepeda Motor Berbasis Mikrokontroler dan Modul GSM - Deri Andesta; Rian Ferdian (Universitas Andalas, 2018)
This study aims to create a security system that can work when motorcycles are parked or are being driven. Most congenital motorcycle security systems work only when the motor is parked, such as the security of the ignition key and the handlebar lock. In fact, not infrequently theft is done by robbing a motorcycle that is being driven by owner. Then made a system using Arduino microcontroller platform, GSM SIM800L module and mobile device. The system created consists of three MODE, the MODE PARKIR, MODE JALAN and MODE MANUAL that can be selected through mobile devices with Bluetooth connection. In MODE PARKIR there are two sensors that detect the theft action, the vibration sensor SW420 and Voltage sensor. If the ignition key is successfully broken or there is a motorcycle on the motorcycle GSM SIM800L module will give notification in the form of SMS and phone call. For Roadside mode the motorcycle ignition system will be activated automatically and the owner can directly use the vehicle without having to manually activate the ignition. When the motorcycle is seized the owner can turn off the vehicle engine by pressing the Stop button on the mobile device and GSM module SIM800L will send the coordinates of the nearest BTS.